Correlation of Tumor-infiltrating Lymphocytes with Tumor Staging and Grading in Breast Carcinomas: A Retrospective Study - Mohit Kumar; Chaitra Eshwaraiah; Athira K P; Shashidhar Rudrappa (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
Background and aim: The global breast cancer mortality rate has increased by 0.23% per year globally, with a statistically significant increase in the age group under 50 and 70+. The present study evaluated Tumor-infiltrating lymphocytes(TIL) in breast carcinoma and correlated TIL with tumour stage, grade, and lymph node metastasis. Material and methods: A retrospective study was conducted on 66 cases of modified radical mastectomy specimens of invasive breast carcinoma. The corresponding patients' clinicopathological details like age, location, laterality, tumour size, and lymph node involvement were retried from case sheets. The histopathological reports and H&E slides were reviewed again. The representative H&E stained section of each case was selected, and TIL assessment was done based on the International TIL Working Group (ITILWG) recommendations.Results: A total of sixty-six cases were included in our study. Out of 66 cases, the majority were seen in the age group between 51-60 years, which is 36.4%. Forty-one cases ( 62.1%) out of 66 were in size groups of 2- 5 cm. 86.4% ( 57 cases) were invasive ductal breast carcinoma. On invasive tumour lymphocyte (TIL) evaluation, grade I was noted in 22 cases, grade II in 33 cases, and 11 in grade III. Conclusions: Our study validates the method of histomorphological evaluation of TILs proposed by the International TIL Working Group (ITWG) 2014 in the Indian population and explores its role as a novel prognostic immune biomarker. Our analysis significantly correlated with tumour size, lymph node status, SBR grading, and histological types.